(untitled) (Journal of Hama University, 2025)
Deals with this research as a male awareness as an informed of non-literary cognitive complaints for public cultural gravity, the cultural reference is the greatest appointment to understand the text when the signal is lost This research has highlighted that male. Consciousness is not a detailed abstract from the general cultural context, but is to be aware of a fragmentary freegoing gain. The research was that male awareness references are in fact intensifying and deepening semantic shipment and cultural pigment through the nature of the social intellectual configuration that is reflected on each individual in society and explained the overlap of the pillars and cultural references We therefore submitted this consideration of access to content through induction of male awareness and transit references to participants from cultural influences.